Detection of antimicrobial compounds from Parmotrema tinctorum lichen from lead contaminated locations - WAHYU AJI MAHARDHIKA; LISDAR IDWAN SUDIRMAN; SETYANTO TRI WAHYUDI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Mahardhika WA, Sudirman LI, Wahyudi ST. 2025. Detection of antimicrobial compounds from Parmotrema tinctorum lichen from lead contaminated locations. Biodiversitas 26: 3071-3079. Parmotrema tinctorum lichen is found in various locations and can be used as a tolerant bioindicator. Based on previous research, it is known that there is a high content of lead (Pb) in the thallus of P. tinctorum found in the Mekarsari Fruit Garden. The aim of this study was to determine the relationship between lead concentration and the activity of antimicrobial compounds from thallus P. tinctorum. Thallus samples were collected from a Pb-contaminated sites, followed by analysis of Pb content. The thalli were then extracted and tested for antimicrobial activity, followed by partial purification and characterization of the antimicrobial compounds. The highest Pb content was found in zone 3 in Mekarsari (MZ3), amounting to 15.64 ppm, followed by zone 2 (MZ2) with 14.72 ppm, zone 1 (MZ1) with 12.86 ppm, and at Mangrove Batu Bedhil (MBB) as a control with 3.42 ppm. The crude extract was able to inhibit all test microbes, and its activity against Propionibacterium acnes showed a significantly different result compared to its activity against the other microbes. In the dilution test of the extract up to 10? against P. acnes, the MZ3 extract still produced a clear zone, whereas the other extracts showed no activity. The results of TLC-bioautography showed that the MZ3 crude extract had an Rf value of 0.52-0.81, and MBB had an Rf value of 0.68-0.91. The antibacterial test of crude extract and preparative fractions of MZ3 and MBB was able to inhibit Bacillus subtilis G and P. acnes, however, there was a decrease in antimicrobial activity, presumably due to Pb being adsorbed onto the adsorbent during preparative TLC. Further research is needed to re-evaluate the appropriate adsorbent for purification of active compound containing lead.